Eosinophilic esophagitis and achalasia – just a coincidence? - Frieling, Thomas; Heise, Jürgen; Kreysel, Christian; Blank, Michael; Hemmerlein, Bernhard; Beccu, Lothar; Kuhlbusch-Zicklam, Rita (Zeitschrift für Gastroenterologie, 2019)
Background Eosinophilic esophagitis (EoE) is detected frequently in dysphagia and noncardiac chest pain. Management of patients with EoE may be complicated because EoE is associated frequently with esophageal motility disorders. We present the rare case of esophageal achalasia (EA) associated with eosinophilic infiltration and a literature review.Material and methods A patient with dysphagia and eosinophilic infiltration referred to our clinic underwent standardized diagnostic work-up including symptom questionnaire, esophagogastroduodenoscopy (EGD) with esophageal biopsies, barium swallow, high-resolution esophageal manometry, and combined intraluminal 24-hour pH-impedance testing (pH/MII).Results The patient had an Eckardt score of 8. EGD and mucosal biopsies showed typical EoE with > 15 eosinophil leucocytes per high-power field. Barium swallow revealed typical sign of achalasia. HREM indicated EA type 2 according to the Chicago classification. PH/MII was normal. Oral and systemic corticoid therapy were without effect. After successful treatment by pneumatic dilation of the cardia, symptoms relieved and eosinophilic infiltration returned to normal.Conclusion The results suggest that the patient had primary EA associated with eosinophilic infiltration and that the combined occurrence of these rare diseases is not just a coincidence.
Keywords: dysphagia; regurgitation; noncardiac chest pain; NCCP; eosinophilic esophagitis; achalasia; esophageal motility disorders